Karawo Ornamental Variety Based on Gorontalo Curtural Phenomenon - Rumambie, W P; Subarna, A D (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The research objective was to see the cultural phenomena that occurred in Karawo embroidery in Gorontalo. Karawo is a typical traditional cloth from Gorontalo which is made by handicrafts. Karawo itself has a unique way of doing it, such as making karawo which requires patience and thoroughness, making karawo takes one week to make one karawo that is ready to use. To support the research, we use descriptive methods and the data collected in the preparation of journals are analyzed descriptively, data collection is also in the form of observations and interviews with traditional stakeholders and karawo embroidery designers. The results show that there is a change in cultural phenomena in the karawo embroidery motifs today, in contrast to the motifs in the past that used cultural motifs based on cultural philosophical values or natural motifs. This is due to the motives that continue to develop and shift to a more modern direction and no longer depend on natural motifs, then adjust to what consumers like. Of course, this affects the making of the karawo embroidery motifs today, which no longer use traditional stakeholders for one motive. The conclusion of the research is to find that the handicrafts of karawo embroidery have shifted to a more modern direction.